(untitled) (Global Journal of Human-Social Science, 2016)
City of Edmonton Alberta Canada Mental Health program designed through various organizations such as the University of Alberta Edmonton Public and Catholic School Board for students staffs and community people I focused on student mental health initiatives in Edmonton as a university student The University of Alberta Mental Health Program has been designed through various service providers such as Wellness Services Peer Group Education Clinical Services Aboriginal Student Group Interfaith Religious Services Sexual Assault Services etc they are working for university students staffs and faculty members including community people through their various programs such as